Mercury Anomalies Link to Extensive Volcanism Across the Late Devonian Frasnian–Famennian Boundary in South China - Zhang, Jiawei; Deng, Changzhou; Liu, Weipeng; Tang, Zuoqi; Wang, Yue; Ye, Taiping; Liang, Weian; Liu, Lingyun (Frontiers in Earth Science, 2021)
The Late Devonian Frasnian–Famennian (F–F) mass extinction has been long-time debated by non-volcanic causes, extra-terrestrial impacts, and large igneous province (LIP) eruptions. To better understand the ultimate cause of the F–F mass extinction, here we investigate the chemostratigraphy of mercury (Hg) and total organic carbon (TOC) on two marine F–F strata in the Dushan area, South China. In both sections, high Hg and Hg/TOC anomalies were observed near the F–F boundary. These anomalies are in line with those recently observed in Morocco, Germany, Poland, and north Russia, suggesting a global Hg flux. The Late Devonian LIP eruptions, which are believed to have emitted massive amounts of Hg, could be responsible for the global Hg and Hg/TOC anomalies around the F–F boundary. The observed Hg and Hg/TOC anomalies coincide with the extinction of Frasnian fauna in the Dushan area, implying a causal link between the Viluy, Kola, and Pripyat-Dnieper-Donets LIP eruptions and the F–F mass extinction.